Infrared Thermography as a Non-Invasive Tool to Assess Health Bio-Marks in University Students - Muhammad Khalid, Muhammad Khurum Ibrahim, Zeenat Zafar, Mudassar Maqbool, Muhammad Musadiq Idris, Sheikh Muhammad Azam, Shakeel Ahmad, Shoaib Hassan, Shazia Bibi, Ghulam Mustafa, Khadija Fatima, Yasir Mehmood, Muhammad Imran, Shaikh Muhammad Abdullah, Has (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To evaluate the relationship between cortisol concentrations (ng/ml) with body temperature, digital thermometer and thermal infrared gun (˚C). Infrared Thermography is a new and revolutionary way of measuring body temperature. Methodology: In this study data is collected about 65 individuals and extract blood samples from 50 students (25 males and 25 females). Results: Non-significant negative correlation was observed between cortisol concentrations (ng/ml) with body temperature of IRT of right eye-maximum (CC = -0.100; P = 0.490). Non-significant negative correlation was observed between cortisol concentrations (ng/ml) with body temperature of IRT of left eye-maximum (CC= -0.099; P = 0.495). Non-significant negative correlation was observed between cortisol concentrations (ng/ml) with body temperature of IRT of forehead-maximum (CC = -0.124; P = 0.413). A non-significant negative correlation is also observed between cortisol concentration (ng/ml) with body temperature of IRT of mean of left eye, thermal infrared gun and digital thermometer (˚C). Conclusion: Overall non-significant negative correlation is also observed between various concentrations with body temperature. Keywords: IRT, Cortisol, Body temperature, Digital thermal temperature, Infrared gun temperature